Leadership and management in UK medical school curricula. Issue 7 (10th October 2016) - Jefferies, Richard; Sheriff, Ibrahim H.N.; Matthews, Jacob H.; Jagger, Olivia; Curtis, Sarah; Lees, Peter; Spurgeon, Peter C.; Fountain, Daniel Mark; Oldman, Alex; Habib, Ali; Saied, Azam; Court, Jessica; et al.
Abstract : Purpose: Although medical leadership and management (MLM) is increasingly being recognised as important to improving healthcare outcomes, little is understood about current training of medical students in MLM skills and behaviours in the UK. The paper aims to discuss these issues. Design/methodology/approach: This qualitative study used validated structured interviews with expert faculty members from medical schools across the UK to ascertain MLM framework integration, teaching methods employed, evaluation methods and barriers to improvement. Findings: Data were collected from 25 of the 33 UK medical schools (76 per cent response rate), with 23/25 reporting that MLM content is included in their curriculum. More medical schools assessed MLM competencies on admission than at any other time of the curriculum. Only 12 schools had evaluated MLM teaching at the time of data collection. The majority of medical schools reported barriers, including overfilled curricula and reluctance of staff to teach. Whilst 88 per cent of schools planned to increase MLM content over the next two years, there was a lack of consensus on proposed teaching content and methods. Research limitations/implications: There is widespread inclusion of MLM in UK medical schools' curricula, despite the existence of barriers. This study identified substantial heterogeneity in MLM teaching and assessment methods which does not meet students' desired modes of delivery. Examples of national undergraduate MLM teaching exist worldwide, and lessons can be taken from these. Originality/value: This is the first national evaluation of MLM in undergraduate medical school curricula in the UK, highlighting continuing challenges with executing MLM content despite numerous frameworks and international examples of successful execution.